The Effect Of Corporate Social Responsibility, Audit Quality, And Leverage On Tax Aggressiveness - Jovianto, Jonathan Levy; Adib, Noval (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This research examines the influence of corporate social responsibility, audit quality, and leverage on tax aggressiveness. This study uses multiple regression analysis methods. The sample in this research consists of 73 companies listed in the LQ45 on the Indonesia Stock Exchange for 2021-2023. This research provides empirical evidence that corporate social responsibility and audit quality variables do not negatively affect tax aggressiveness, while the leverage variable positively influences tax aggressiveness. Furthermore, referring to the research results, investors must consider a company's tax aggressiveness level in their investment decisions to avoid potential risks from overly aggressive tax planning practices. Additionally, companies need to control their tax planning practices to prevent them from becoming too aggressive, which could lead to illegal tax planning practices. On the other hand, the government can benefit from this research as an additional reference and insight for setting tax regulations, so that companies and the government can collaborate to achieve more optimal tax revenue.